The dynamics of trypanosome infections in natural populations of tsetse (Diptera: Glossinidae) studied using wing-fray and ovarian ageing techniques - Leak, S.G.A.; Rowlands, G.J. (Cambridge University Press, 1997)
Trypansosome infections in approximately 110,000 tsetse of 12 species or subspecies, at sites in six African countries, were studied over various periods from 1983 to 1994. Infection rates ranged from 0.2 percent in Glossina fuscipes quanzensis Pires at a site in Zaire, to 18 percent in Glossina tabaniformis Westwood at a site in Gabon. Statistical models were fitted to data for nine species or sub-species of tsetse (G. pallidipes Austen, G. morsitans morsitans Westwood, G. morsitans submorsitans Newstead, G. fuscipes fuscipes Newstead, G. fuscipes quanzensis Pires, G. palpalis palpalis Robineau-Desvoidv, G. palpalis gambiensis Vanderplank, G. tanchinoides Westwood and G. tabaniformis Westwood), recorded across eight sites. The prevalence of mature trypanosome infections increased with age, as determined by wing-fray category, for both Trypanosoma vivax-and T. congolense-type infections, although for G. palpalis, G. tabaniformis and G. tachinoides the rate of T. vivax-type infections decreased in older age categories. Infection rates for T. brucei were very low and statistical analysis was not possible for this species. Overall prevalences of Trypanosoma vivax-type infections were significantly higher in female than male flies in four tsetse species; G. pallidipes, G. palpalis, G. tabaniformis and G. tachinoides. At sites where ovarian ages were also determined, close correlations between wing-fray category and ovarian age were found.